Combustion characteristics of trimethyl borate, diesel, and trimethyl borate-diesel blend droplets. (December 2022) - Yontar, Ahmet Alper; Özgüner, Ayşe Gizem; Adıgüzel, Mehmet Ali; Üstün, Deniz
Abstract: In this study, droplet tests were carried out for pure and blended forms of diesel fuel, which is the traditional fuel, and trimethyl borate fuel, which is new generation fuels. In this context, the evolution of fuel droplet diameter, flame structure, and flame temperature over time was observed using a high-speed camera and a thermal camera simultaneously. Measurements were made for the addition of 20%, 40%, 60%, and 80% trimethyl borate fuel to diesel fuel in fuel blends. The curves of the time-dependent change of the dimensionless square of the droplet diameter (D/D0 ) 2 of the fuel droplets considered in the study, in general, have been determined to comply with the D 2 -law. Also, as the amount of diesel rose, there were high changes in droplet distortion and high deviations from the hemispherical geometry, and also elongation in the dominant shape droplet shape changed times. While the highest flame temperature was monitored by the thermal camera in the flame formed by the trimethyl borate droplet, as the amount of diesel fuel in the mixture increased, the maximum flame temperature decreased, but the burning time of the droplet was prolonged. On the other hand, the shortest ignition delay was measured for trimethyl borate, while the longest ignition delay time was detected for diesel fuel droplet. In general, it has been observed that the addition of trimethyl borate reduces the ignition delay, shortens the extinction time, and increases the temperature during combustion compared to diesel. Highlights: The burning time was prolonged as the amount of diesel in the blend increased. The highest flame temperature was observed for the trimethyl borate droplet. As the amount of diesel in the blend raised, the flame temperature decreased. The shortest ignition delay was measured for trimethyl borate droplet. As the amount of trimethyl borate raised, droplet deformation was upsurged.